First-line durvalumab therapy alone or in combination with tremelimumab for metastatic head and neck squamous cell carcinoma: A cost-effectiveness analysis. - Huijuan Li; Xueyan Liang; Shiran Qin; Xiaoyu Chen; Liju Huang; Yan Li (PLoS ONE)
Objective In patients with recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC), the KESTREL study evaluated durvalumab with or without tremelimumab, as well as the EXTREME regimen (platinum, 5-fluorouracil, and cetuximab). In the first-line treatment of R/M HNSCC, no data are available regarding the cost-effectiveness of these immunotherapeutic agents. Based on third-party payers' perspectives in the United States, we compared durvalumab and tremelimumab in this setting. Methods The projected costs and outcomes over a 12-year period were calculated using a three-state partitioned survival model with an annual discount of 3%. Long-term extrapolation of KESTREL was used to model progression-free and overall survival. Life-years, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratios (ICERs), incremental net monetary benefits (INMBs), and incremental net health benefits (INHBs) were calculated. The uncertainty and stability of the model were examined using one-way and probabilistic sensitivity analyses. Results In the overall population, EXTREME was dominant compared to durvalumab plus tremelimumab (Durva-Treme). Compared to durvalumab monotherapy (Durva-mono), EXTREME resulted in an increase of 0.037 life-years and 0.012 QALYs, as well as an increase in cost of $85,420 per patient. The corresponding ICER was $7,310,878/QALY, and the INHB and INMB values were negative at a willingness to pay threshold of $150,000/QALY. Furthermore, Durva-mono dominated EXTREME or Durva-Treme in patients with high PD-L1 expression. When compared with EXTREME, Durva-Treme had an ICER of $560,406/QALY. Durva-Treme was unlikely to be cost-effective. The HRs for OS, PFS, and drug costs (cetuximab, tremelimumab, and durvalumab) were most sensitive to the model. The results of the sensitivity analyses were similar, suggesting the robustness of the findings. Conclusions Durva-mono is a cost-effective treatment strategy for patients with R/M HNSCC, particularly in patients with high PD-L1 expression, compared with EXTREME or Durva-Treme. Cetuximab cost reduction may benefit the EXTREME regimen economically. Nevertheless, Durva-Treme provided fewer survival gains at substantial additional costs; therefore, it is unlikely to be a cost-effective option.